2022
DOI: 10.4103/jisp.jisp_150_21
|View full text |Cite
|
Sign up to set email alerts
|

Salivary tumor necrosis factor-alpha levels in periodontitis associated with diabetes mellitus after low level laser therapy as an adjunct to scaling and root planning

Abstract: Context: Tumor necrosis factor-alpha (TNF-α) has been shown to play a critical role in the pathogenesis of periodontitis and diabetes. Nonsurgical periodontal therapy was shown to reduce inflammation and improves glycemic status. Recently, adjunctive low level laser therapy (LLLT) has been shown to alter the inflammatory process. Aim: To evaluate and compare the alteration in TNF-α levels before and after treatment in patients with periodontitis with and without type 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Regarding diabetes chronic periodontitis, three teams each published 2-3 studies: Chava et al. ( 34 , 35 ), Haaki et al. ( 36 , 37 ), and Obradovic et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding diabetes chronic periodontitis, three teams each published 2-3 studies: Chava et al. ( 34 , 35 ), Haaki et al. ( 36 , 37 ), and Obradovic et al.…”
Section: Resultsmentioning
confidence: 99%
“…Among studies that examined the gingival index, plaque index, and clinical attachment level, 75% reported improvements in at least one of these parameters. Four studies reported negative results: one had the highest fluence ( 144 ), one had the highest exposure frequency [once a day for 8 weeks ( 35 )], one had poorly described illumination parameters and a wavelength beyond the infrared range ( 142 ), and one had four PBM exposure sites ( 148 ), whereas most studies reported one to two exposure sites. Finally, the ideal parameters could involve a single exposure or exposure over 2 to 3 days, on one to two sites in direct contact with gingival tissue or intra-pocket, with a fluence of 1 to a few J/cm², continuous or pulsed laser illumination, and a wavelength range of 650 to 1064 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, periodontitis is mainly treated by subgingival scaling and root planing (SRP), which removes tartar and plaque from the root surface within periodontal tissues through subgingival ultrasonic instruments 3) . SRP can relieve inflammation and promote tissue healing by destroying and removing the subgingival plaque biofilm and establishing a biocompatible root 4) . However, SRP alone has poor efficacy since occlusal traumas occur in most patients with periodontitis due to an excessive occlusal force or an abnormal lateral occlusal force, thus exacerbating periodontal destruction.…”
Section: Introductionmentioning
confidence: 99%